Pengaruh Capital Expenditure, Firm Size, dan Operating Cash Flow Terhadap Tingkat Inovasi Perusahaan di Sektor Teknologi yang Terdaftar di BEI - Pambudi Setyadi; Helisa Noviarty; Haryono Haryono (Jurnal Akuntansi, Ekonomi dan Manajemen Bisnis, 2025)
This study aims to analyze the effect of capital expenditure, firm size, and operating cash flow on the level of innovation among technology sector companies listed on the Indonesia Stock Exchange (IDX). A quantitative approach was employed using multiple linear regression analysis on secondary data obtained from the annual financial reports of 30 companies for the period 2022–2024. The results indicate that although capital expenditure, firm size, and operating cash flow tend to have a positive influence, they do not have a statistically significant effect on corporate innovation. This suggests that these financial factors do not directly guarantee an increase in innovation. The study contributes to a deeper understanding of the factors influencing innovation in the technology sector, highlighting the importance of external elements such as innovation culture and organizational structure. These findings are expected to provide insights for companies and relevant stakeholders to adopt a more holistic approach in fostering innovation